2023
DOI: 10.3390/ijms241411759
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of CD73 in Cancer

Abstract: The search for new and effective treatment targets for cancer immunotherapy is an ongoing challenge. Alongside the more established inhibitory immune checkpoints, a novel potential target is CD73. As one of the key enzymes in the purinergic signalling pathway CD73 is responsible for the generation of immune suppressive adenosine. The expression of CD73 is higher in tumours than in the corresponding healthy tissues and associated with a poor prognosis. CD73, mainly by the production of adenosine, is critical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…PD-L1 was chosen for these analyses since immune checkpoint inhibitors (ICI) targeting the PD-L1/PD-1 association are used for treatment of a subset of NSCLC patients and given that it has been reported that PD-L1 expression on EVs (both small- and large-sized EVs) isolated from plasma or serum of NSCLC patients may hold prognostic potential. , We also examined CD73, which is well known to cause an immune suppressed tumor microenvironment and which recently was demonstrated to take part in adenosine generation when expressed on EVs/exosomes isolated from cancer patient serum, thereby also impacting on ICI treatment response. …”
Section: Resultsmentioning
confidence: 99%
“…PD-L1 was chosen for these analyses since immune checkpoint inhibitors (ICI) targeting the PD-L1/PD-1 association are used for treatment of a subset of NSCLC patients and given that it has been reported that PD-L1 expression on EVs (both small- and large-sized EVs) isolated from plasma or serum of NSCLC patients may hold prognostic potential. , We also examined CD73, which is well known to cause an immune suppressed tumor microenvironment and which recently was demonstrated to take part in adenosine generation when expressed on EVs/exosomes isolated from cancer patient serum, thereby also impacting on ICI treatment response. …”
Section: Resultsmentioning
confidence: 99%
“…Other proteins in Table include markers for cancer that have been reported to play an important role in previous studies. , These include several of the annexins, known markers related to different types of cancer, especially AnnexinA2. Also, included among cancer-related proteins are vimentin, , an important EMT marker and CD29 , also known as integrin beta 1 (ITGB1), which is often associated with aggressive cancers. CD73, also known as NT5E, is involved in cancer-related processes and upregulated in many cancers, making it an important marker for cancer . It is a key molecule in cancer regulation and development and is involved in tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…CD73, also known as NT5E, is involved in cancer-related processes and upregulated in many cancers, making it an important marker for cancer. 43 It is a key molecule in cancer regulation and development and is involved in tumor progression. These proteins are detected in the EVs from all three cell lines and the mix of these cell lines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5’-NT (5’-nucleotidase, also known as CD73) is an enzyme that plays a significant role in cancer, particularly in the context of the tumor microenvironment and immune response 29 . 5’-Nucleotidase (CD73) protein expression in cancer is closely linked to the tumor microenvironment and immune response, and high levels of CD73 can promote an immunosuppressive environment, allowing cancer cells to grow and metastasize 29 . It is a potential target for cancer immunotherapies, and its expression can serve as a diagnostic and prognostic marker for certain cancer types.…”
Section: Discussionmentioning
confidence: 99%